(untitled) (Revista de Artes Marciales Asiáticas, 2024)
Taekwondo, designated as the official ‘national sport of the Republic of Korea,’ has been a source of pride and a point of reference for the Korean people. A great variety of academic articles and books have been published over the last decades about the general historical formation of taekwondo; however, the topic of taekwondo’s institutionalization in South Korea has been largely neglected or ignored. At some point in their lives, almost every South Korean, particularly within the male population when they enter military service, undergoes some form of taekwondo training. No other country in the world integrates martial arts in such a wide-ranging manner. Hence, this article aims to explain the broad integration of taekwondo into the public and higher education system and the military of South Korea. Subsequently, this study details taekwondo as a career opportunity in South Korea, which is highly unique among nations. Lastly, this article focuses on the broadening and specialization of taekwondo activities with the spread and popularization of ‘demonstration’ and ‘forms’ taekwondo. In summary, this article aims to explore these phenomena and contribute new insights to the field of Taekwondo Studies.